Asparagine-linked glycosylation in Saccharomyces cerevisiae: genetic analysis of an early step. - Barnes, G (1984)
Asparagine-linked glycosylation is a form of covalent modification that distinguishes proteins that are either membrane bound or are in cellular compartments topologically outside of the cell from those proteins that remain soluble in the cytoplasm. This type of glycosylation occurs stepwise, with core oligosaccharide added in the endoplasmic reticulum and subsequent modifications occurring in the golgi. We used tunicamycin, an inhibitor of one of the earliest steps in the synthesis of N-linked oligosaccharide, to select for mutants that are resistant to this antibiotic. Genetic, biochemical, and physiological experiments led to the following conclusions. The synthesis of N-linked oligosaccharide is an essential function in cells. In contrast to mammalian cells, yeast cells do not transport tunicamycin by a glucosamine transport function. We identified a gene, ALG7, that is probably the structural gene for UDP-N-acetylglucosamine-1-P transferase, the enzyme inhibited by tunicamycin. Dominant mutations in this gene result in increased activity of the transferase and loss of the ability of the cell to sporulate. In addition, we identified another gene, TUN1, in which recessive mutations result in resistance to tunicamycin. The ALG7 and TUN1 genes both map on chromosome VII.